Penatalaksanaan penyakit pre-diabetes mellitus pada dokter keluarga di Kota Manado - Ariel Arina; Henry Malcom Frank Palandeng; Frelly Valentino Kuhon (UNIVERSITAS SAM RATULANGI, 2022)
Introduction: Pre-diabetes is a condition in which blood sugar levels are higher than normal but not high enough to be called diabetes. Control of DMT2 disease requires a holistic approach to meet the needs of the community through the pre-diabetes group, namely family physicians. Studies have found that general practitioner that have limited knowledge of risk factors for pre-diabetes screening, laboratory diagnostic criteria for pre-diabetes, and management recommendations for patients with pre-diabetes contributing to an inadequate diagnosis of pre-diabetes. Purpose: To find the behavior of family physicians in the management of chronic disease pre-diabetes mellitus in Manado City. Methods: This research is a descriptive study using a cross-sectional design. Result: The results showed that the knowledges level of family physicians in Manado City was in the good category totaling 31 doctors (100%), the attitudes level of family physicians in the good category with 31 doctors (100%), and the practice level of family physicians was in the good category with 31 doctors (100). Conclusion: Based on the results of the study, family physicians in Manado have good knowledge, attitude, and practice about pre-diabetes. Keywords: pre-diabetes, behavior, family physicians